Records Management Practices and Business Sustainability of Small-Scale Business: A Case Study of Kindly Services. - Ainebyoona, Ritah (Kabale University, 2024)
This study was focused on records management practices and business sustainability of small-scale businesses in the Rukiga district. The study employed cross sectional survey design across respondents of Kindly Service. The study findings indicate that there were causes of poor records management practices on sustainability of small scale business as they include; lack of accountability, lack of knowledge, greediness for money, exposure of skills, lack of proficiency, emblements of funds, and heavy taxes. 81% of the respondents agreed that embezzlement of funds is one of the causes of poor records management sustainability of small-scale businesses. Findings of the study indicate that there were contributions of records management practices towards financial sustainability of small-scale businesses as they include; effective financial management, follow-ups in books of accounts, evaluation of proposed source, easy workload, support of rural livelihoods, easy accountability, and business analysis. 78% of the respondents agreed business analysis was one of the contributions of records management toward the financial sustainability of small-scale businesses. The findings of the study indicate that there were challenges faced by small-scale businesses including; limited access, rapid, rapid changes and advancement in technology, absence, of policies, lack of diversity and verification, competition from existing firms, and lack of accountability. 80% of the respondents indicate that lack of diversity and verification was a major challenge faced by records management practices on the sustainability of small-scale businesses. The study recommends that the government should restrict laws on the businesses that do not have proper records management practices, this encourages more to exercise it hence better financial sustainability as their operations are concerned and all business owners, operators, and customers should ensure that colleagues in department as business system is concerned are having records management in order to retain their financial sustainability as advisor and IGG’s (Inspector General Government) to them.